Which Augustine? The Naming of the Abbey and Church of St Augustine, Bristol - Higgins, David H. (The journal of ecclesiastical history, 2012)
The abbey of St Augustine was named for Augustine ‘Apostle of the English’, as was its associated parish church, but was governed from its foundation by canons of the rule of St Augustine of Hippo. The two Augustines in the equation were a source of confusion. A reconstruction of the abbey's lost liturgical calendar suggests that the chapter sought to exploit this uncertainty in the matter of the foundation history of their abbey, with the aim of displacing, in the popular mind, the humble ‘English’ saint of the dedication in favour of the ‘Latin’ founder of the canons' rule.